REALISM IN WORLD LITERATURE AS A LITERARY FLOW, DIRECTION, STYLE, GENRE AND ARTISTIC TYPE (TAMADDUN NURI JURNALI, 2024)
In this article, the concept of realism in literature is primarily used in relation to the literary direction, type of literature, method, genre, style and flow, and it is said that it is a rich concept in essence. The term “realism” in literature is recognized as a period of fundamental changes in various folk literary studies. The features defining the uniqueness of this period are considered.